Vpliv dejavnika tumorske nekroze-alfa na izločanje interlevkina-6 iz človeške mišice v kulturi - Prelovšek, Oja (Medicinski razgledi, 2004)
Tumor necrosis factor-a (TNF-alpha) is a pleiotropic cytokine which, as a partof complex cytokine system, controls the synthesis and expression of othercytokines and their receptors through the activation of cytokine cascades. The aim of our study was to test the effects of TNF-alpha on the secretion of interleukin-6 (IL-6) from cultured human muscle. We studied theseeffects before and after the fusion of myoblasts into multinucleated myotubes. Cultures, prepared from satellite cells isolated from the muscle pieces routinely discarded at some orthopaedic operations were treated with TNF-alpha at three different concentrations. We found that TNF-alpha increasesthe IL-6 secretion in a concentration dependent manner. Quantitatively, secretion from myotubes exceeded the secretion from myoblasts indicating that secretion is differentiation stage-dependent. The presence of TNF-alpha receptor was confirmed by Western blot. Apoptosis, followed by DNA fragmentation, remained unchanged. Our results support the concept that skeletal muscles actively participate in cytokine signalling in critical clinical conditions.
Keywords: Interlevkin-6; Muscle, Skeletal; Laktatna dehidrogenaza; Drug Effects; Mišica skeletna; Secretion; Mišična vlakna; Tumor Necrosis Factor; Tumor nekrotizirajoči faktor; Interleukin-6; Muscle Fibers; Apoptoza; Lactate Dehydrogenase; Celica, štetje; Celične kulture; Cells, Cultured; DNA , razdrobitev; Cell Count; Encimsko-vezani imunosorbentni test; Enzyme-Linked Immunosorbent Assay; Receptorji, tumorje nekrotizirajoči faktor; Receptors, Tumor Necrosis Factor; skeletne mišice; Blotting, Western; Dna Fragmentation; mioblasti; Apoptosis; fiziologija; Blot, Western; drug; zdravila; učinki; tkivne kulture